KUALITAS AIR DANAU MANINJAU UNTUK BUDIDAYA IKAN KERAMBA DI DESA KUBU BARU KABUPATEN AGAM SUMATERA BARAT - Rendani, Friska - (STKIP PGRI Sumbar, 2014)
Water is a natural resource that is essential for life on earth. The source of the water there is obtained from groundwater, springs, rivers, lakes, and sea water. The quality of water is water that meets the quality standards that vary depending on the destination user. While water is a basic requirement in fish farming.In the waters of the lake ecosystem are abiotic and biotic factors (producers, consumers, and decomposers) are forming a mutual relationship and mutual influence. Waters of the lake is one of the freshwater ecosystems that exist on the surface of the earth.This study aims to determine the water quality of Lake Maninjau for fish farming cages. The method used is descriptive analysis with the aim of making a picture of systematic factual and accurate information regarding the feasibility of water quality based on physical parameters (odor, color, and temperature) qualifies standards, biological, and chemical (pH, DO, fofat, NH3). Research location in Lake Maninjau in Kubu Baru village by establishing three sample points, namely: Upper section (sample A), the middle (sample B), the downstream section (sample C) qualifies standards. Based on the results: (1) in terms of physical water quality (odor, color, temperature) has met the standards for fish farming cages, (2) the quality of water contained in the biological 75MPN / 100ml coliform bacteria, which means suitable for fish farming cages , (3) water quality in terms of chemical properties (pH, DO, phosphate, NH 3) for pH and dO are not suitable for fish farming cages because of its high content of pH and dO, while for phosphate and NH3 unsuitable for fish farming because it does not exceed Karamba quality standards.